Rural digitalization in China - E. F. Avdokushin; Wang Zhui (Мир новой экономики, 2022)
The article shows how the process of the Chinese economy’s digitalization, which began in urban areas, manufacturing, and rich provinces of China, now starts to engulf the rural areas. The digital gap between certain provinces and between urban and rural areas must be liquidated as part of the Chinese government’s strategy to make the country a thriving innovation society by the mid‑21st century. The article lays out basic directions and means of bridging the digital gap between urban and rural areas and several aspects of digital modernization in China’s agriculture. A particular focus is on developing green, environmentally friendly agriculture and the birth of a green way of life in rural areas and smart villages.